Problematika Kurikulum Pendidikan Islam - Mujibur Rohman (Madaniyah, 2015)
The curriculum contains the content, objectives, methods, and educational evaluation tools. Islamic education curriculum has meaning as a series of programs that direct the teaching and learning activities are planned with the systematic and trending purposes, as well as describe the ideals of Islam. Islamic education curriculum has 3 types of curriculum; pragmatic curriculum, curriculum theoretical and theological curriculum. The success of religious education viewed from three principal indications, the success of knowledge transfer, the transfer value, transferring skills. The first part related to cognitive knowledge. The second part related to the value of good and bad, students are directed to love the virtues and values hate crime, the third part related to the real action.